After the Fall : How Humpty Dumpty Got Back Up Again : a Story - Santat, Dan (New York : Roaring Brook Press, 2017)
After falling off the wall, Humpty Dumpty is very afraid of climbing up again, but is determined not to let fear stop him from being close to the birds.
Keywords: Characters and characteristics in literature -- Juvenile fiction; Determination (Personality trait) -- Juvenile fiction; Fear -- Juvenile fiction; Characters in literature -- Fiction; Determination (Personality trait) -- Fiction; Fear -- Fiction